PLASTIC DEBRIS USAGE BY TUBE-BUILDING POLYCHAETE Diopatra cuprea COMPLEX: Uso de lixo plástico pelo complexo de espécies do poliqueta tubícola Diopatra cuprea - Cruz da Rosa, Leonardo (Arquivos de Ciências do Mar, 2023)
In this short note the plastic debris usage by tube-building polychaete Diopatra cuprea complex in the tube caps decoration is reported for the first time. Soft plastics attached to tube caps were recorded at a tidal flat in the Sergipe River estuary, northeastern Brazil. This interaction probably reflects an adaptation of this polychaete to a highly polluted environment. Keywords: pollution, soft plastics, tube caps, decoration.